Optimization of NPK for curd yield in broccoli (Brassica oleracea) under middle Gujarat condition (Current Horticulture, 2024)
The experiment was conducted to optimise doses of NPK for curd yield in broccoli during rabi 2018-19, 2019- 20 and 2020-21. There were 3 factors i.e. nitrogen @ 100, 150 and 200 kg/ha, phosphorus and potash each @ 50 & 75 kg/ha comprising 12 treatments. Significant increase was found in plant height, plant spread, number of leaves/plant, stem diameter, leaf length, curd weight, curd length, curd diameter, yield /plot, curd yield. The decrease in days to 50% in curd formation and days to final harvest were recorded with different levels of NPK doses. Growth and yield attributes were maximum with 200:75:50 NPK kg/ha which was at par with 150:75:50 NPK kg/ha.
Keywords: Curd; NPK; Growth and yield parameters